Hendra virus infection dynamics in the grey-headed flying fox (Pteropus poliocephalus) at the southern-most extent of its range: Further evidence this species does not readily transmit the virus to horses - Burroughs A.L. (Public Library of Science (PLoS), 2018)
10.1371/journal.pone.0155252